The Effect of Blended Learning to the Students’ Achievement in Grammar Class - Arina Isti'anah (IJEE (Indonesian Journal of English Education), 2017)
ABSTRACT Blended learning is believed to improve students’ understanding in learning second language. The employment of offline and online activities is expected to give better outcome than the traditional face-to-face activities. This article presents how blended learning was applied in an English grammar class and whether it significantly improved students’ achievement after the treatment. The participants involved in this research were 26 students of the the second semester students of the English Letters Department, Sanata Dharma University. A pre-experimental research was conducted by comparing the means of the participants’ scores in both pre-test and post-test. The analysis figured out that there was a significant improvement, proven by the paired t-test analysis. The p-value 0.00 was less than alpha 0.05. This research concluded that blended learning was effective to assist the students to learn English grammar. To strengthen the findings, this research also involved pre-questionnaire and post-questionnaire to understand students’ responses on the use of blended learning. In the end of the semester, most students found that online activities help them comprehend and practice the materials. Students’ reflective journals also revealed that blended learning was able to improve their understanding and interest in learning English grammar.  ABSTRAK Blended learning dipercaya mampu meningkatkan pemahaman siswa dalam memahami bahasa asing. Penggunaan aktifitas offline dan online diharapkan mampu memberi luaran yang lebih baik dibandingkan aktifitas tatap muka secara tradisional. Artikel ini menyajikan bagaimana blended learning diterapkan dalam kelas English grammar dan mengungkapkan apakah blended learning memberikan perbedaan berarti dalam pencapaian mahasiswa sebelum dan setelah perlakuan. Partisipan yang dilibatkan dalam penelitian ini adalah mahasiswa semester dua dari Program Studi Sastra Inggris, Universitas Sanata Dharma. 26 partisipan dilibatkan dalam penelitian ini. Penelitian pra-eksperimen diterapkan dengan membandingkan rata-rata nilai dari peserta dalam pre-tes dan pos-tes. Hasil analisis menunjukkan bahwa terdapat perbedaan signifikan rata-rata dari kedua tes, yang ditunjukkan dengan analisis pasangan t-tes. Nilai p menunjukkan 0.00 dan lebih kecil dari alpha 0.05. Penelitian ini menyimpulkan bahwa blended learning efektif untuk mendampingi mahasiswa belajar English grammar. Untuk memperkuat penemuan tersebut, penelitian ini juga melibatkan pre-kuesioner dan pos-kuesioner. Pada akhir semester, sebagian besar mahasiswa menemukan bahwa aktifitas online membantu mereka memahami dan melatih materi yang mereka pelajari. Jurnal reflektif mahasiswa juga menunjukkan bahwa blended learning mampu meningkatkan kemampuan mereka belajar English Grammar.How to Cite: Isti’anah, A. (2017). The Effect of Blended Learning to the Students’ Achievement in Grammar Class. IJEE (Indonesian Journal of English Education), 4(1), 16-30 doi:10.15408/ijee.v4i1.5697.DOI: http://dx.doi.org/10.15408/ijee. v4i1.5697